(untitled) (Humanis, 2026)
The mosque is a place of worship for Muslims. The existence of the mosque helps in the spread of Islamic teachings. In the Kalimantan region, there are mosques that are used as a place of worship as well as a means of spreading Islam, namely the Sultan Suriansyah Mosque, Kyai Gede Mosque, and Pusaka Banua Lawas Mosque. These three mosques are located in southern Kalimantan. The aim of this research is to find out the pattern of inclination towards the three mosques. This study used a qualitative type with observational data collection at the Sultan Suriansyah Mosque and a literature review at the Kyai Gede Mosque and the Banua Lawas Heritage Mosque. The analysis used in this research is Site Catchment Analysis or Site Coverage Analysis according to Roper (1979) in this analysis there is a relationship between site location and site function. Data analysis was carried out in this study to compare the positions of the three mosques. The results of this study obtained a picture of the layout of the three mosques which were influenced by river culture. In addition, river culture also influences settlement patterns, economic centers, government centers, and the spread of Islam